Facile preparation and dielectric properties of BaTiO3 with different particle sizes and morphologies. Issue 16 (6th April 2023) - Wu, Xinxiao; Zhao, Hepan; Han, Weining; Wang, Zhimiao; Li, Fang; Li, Jing; Xue, Wei
Abstract : BaTiO3 nanoparticles with different sizes and morphologies were prepared by the hydrothermal method with additives, and the dielectric properties of BaTiO3 ceramic sheets were tested. Abstract : BaTiO3 nanoparticles were prepared by the hydrothermal method, and the effect of 1-(propyl-3-methoxysilyl)-3-methylimidazole chloride on the size of BaTiO3 particles was investigated. The obtained BaTiO3 was characterized by XRD, SEM, TEM, and Raman spectroscopy; and the dielectric properties of BaTiO3 ceramic sheets were tested. The results indicate that the spherical BaTiO3 -N prepared without an ionic liquid was in a tetragonal phase with an average particle size of 129 nm. When an ionic liquid was added, the size of the BaTiO3 -IL decreased and the degree of agglomeration increased. In addition, with increasing quantity of ionic liquid, the tetragonal-phase content of BaTiO3 -IL gradually decreased until complete transformation into cubic phase. The dielectric constant of the BaTiO3 -N ceramics was the highest, and the dielectric constant decreased with decreasing BaTiO3 particle size. Moreover, two types of BaTiO3 nanoparticles (bowl- and sea urchin-shaped) were prepared by changing the hydrothermal conditions and additives. The average particle size of the former was 92 nm, the tetragonal-phase content was ca. 90%, and the dielectric constant was large; whereas the sea urchin-shaped BaTiO3 consisted of small particles in the cubic phase, and the dielectric constant was small.